Possitron Emisiot Tomography in the menagement of lung diseasses: Current Aplications and futures perspectives - Dimitrievska D; Zdraveska M; Todevski D; Tushevska-Mitkovska M; Chamurovski N; Arbutina S (Opca Bolnica Teshanj, 2021)
Positron emission tomography (PET) combined with computed tomography (CT) is an established diagnostic modality that has become an essential imaging tool in oncological practice. However, thanks to its noninvasive nature and its capability to provide physiological information, the main applications of this technique have significantly expanded. In the past 20 years, positron emission tomography (PET), usually with 18F-fluoro-2-deoxy-D-glucose (FDG), has become an important imaging modality in patients with lung cancer. PET is a useful technique to characterize the solitary pulmonary nodule, diagnose primary lung cancer, carry out mediastinal and extrathoracic staging, plan radiotherapy, therapeutic response assessment and detect recurrence. PET may help to determine the ideal site for tissue diagnosis as well as predict prognosis. Combined PET and computed tomography (PET / CT) has the best of both worlds of metabolic and anatomic imaging and may provide optimal disease assessment. 18F-labelled fluorodeoxyglucose (FDG) is the most commonly used radiopharmaceutical for PET scanning and demonstrates metabolic activity in various tissues. Since activated inflammatory cells, like malignant cells, predominantly metabolise glucose as a source of energy and increase expression of glucose transporters when activated, FDG-PET/CT can be successfully used to detect and monitor a variety of lung diseases, such as infections and several inflammatory conditions. The added value of FDG-PET/CT as a molecular imaging technique relies on its capability to identify disease in very early stages, long before the appearance of structural changes detectable by conventional imaging. Furthermore, by detecting the active phase of infectious or inflammatory processes, disease progression and treatment efficacy can be monitored.
Keywords: positron emission tomography (PET); PET/computed tomography; lung cancer; tumor staging; therapy response; evaluation of inflammatory and infectious lung diseases